Brand switching behavior on consumer loyalty of branded packed rice in Pangkalpinang City - Fitriyani, Fitriyani; Karsiningsih, Eni; Purwasih, Rati (Department of Agribusiness, Faculty of Agriculture, Universitas Trunojoyo Madura, Indonesi, 2025)
The purpose of this study was to analyze the factors that influence brand switching and consumer loyalty for branded packaged rice. This research was conducted in Pangkalpinang City. The sample was taken using purposive sampling method as many as 100 people. Data analysis using Smart Partial Least Square with the help of SmartPLS 4 software. Price perceptions and product quality have a significant effect on brand switching and loyalty. Perceived price and product quality have an indirect effect on brand switching and branded packaged rice consumer loyalty.